Sharing a Ride on the Commodities Roller Coaster : Common Factors in Business Cycles of Emerging Economies - Fernandez, Andres (IMF Working Papers; Working Paper ;, 2015)
Fluctuations in commodity prices are an important driver of business cycles in small emerging market economies (EMEs). We document how these fluctuations correlate strongly with the business cycle in EMEs. We then embed a commodity sector into a multi-country EMEs' business cycle model where exogenous fluctuations in commodity prices follow a common dynamic factor structure and coexist with other driving forces. The estimated model assigns to commodity shocks 42 percent of the variance in income, of which a considerable part is linked to the common factor. A further amplification mechanism is a 'spillover' effect from commodity prices to risk premia.